Vascular cognitive impairment - Smith, Eric E. (Henry Stewart Talks, 2021)
Definition of vascular cognitive impairment (VCI) and vascular dementia, Epidemiology and pathophysiology of VCI, Causes of VCI, Molecular mechanisms of VCI, Diagnostic approach, Principles of management, Prevention of VCI